PARTISIPASI MASYARAKAT DALAM MEMBAYAR PAJAK KENDARAAN BERMOTOR PADA KANTOR BERSAMA SAMSAT BITUNG - Sari, Cindy Nun; Tulusan, Femmy; Ruru, Joorie Marhaen (JURNAL ADMINISTRASI PUBLIK, 2016)
Abstract : The study is in the context of preparing the thesis for Tier One graduated in the Faculty of Social and Political Unsrat Manado. This study aims to determine the Community's Participation in the Motor Vehicle Tax Paid on call centers Bitung. This study uses descriptive qualitative research in the form of case studies and studies done on the case book. Studi call centers Bitung, while the literature study conducted by collecting data from the literature relevant to the problems of motor vehicle tax. The results showed that the level of community participation as a taxpayer in the motorcycle vehicle has been classified as PKB pay advanced, services performed by the employee Samsat is very well to the public taxpayer, but for better results again should the holding of direct socialization of the SAMSAT.Keywords: public participation, pay PKB